THE EFFECT OF NUTRITION AND DEPRESSION STATUS ON QUALITY OF LIFE IN PATIENTS REQUESTING HEMODIALYSIS - GÜZELŞEN BAKIR, Bahar; GÖBEL, Pınar (Göbeklitepe Medical Science Journal, 2024)
The research was conducted between January and March 2022 at a private dialysis center in Istanbul, involving 80 patients aged 18 to 65 who were undergoing hemodialysis treatment. The objective was to examine the interplay among nutrition, depression, and quality of life. Patient characteristics, anthropometric measurements, and 24-hour dietary records were collected via a questionnaire. The questionnaire included the Short Form-36 Quality of Life Scale (SF-36), Beck Depression Inventory (BDI), and Subjective Global Assessment (SGA). A significant correlation was observed between depression levels and quality of life scores (p < 0.05). However, no significant links emerged between nutritional status, depression, and quality of life (p > 0.05). A notable connection was found between nutritional status and daily energy/macronutrient intake. Patients with good nutritional status had significantly higher intake than those with poor nutritional status (p < 0.05). Statistical analyses revealed significant and non-significant associations among patient characteristics, quality of life, and depression status. This variability is attributed to various psychological and physiological factors influencing hemodialysis patients' quality of life. The results suggest the importance of personalized nutritional support, nutritional education, and regular monitoring of high-risk patients to mitigate malnutrition and enhance patients' quality of life.